SPECIAL RELATIONSHIP TRANSACTIONS AGAINST TAX AGGRESSIVENESS IN PROPERTY COMPANIES WITH INSTITUTIONAL OWNERSHIP AS A MODERATING VARIABLE - Afani, Moh.; Atika, Bunga Filsa; Cahya, Rama Putra Adi; Setyaningsih, Nina Dwi; Murdiansyah, Isnan (Institut Teknologi dan Bisnis Asia Malang, 2024)
This study examines the effect of special relationship sales transactions and special relationship lending on tax aggressiveness with institutional ownership as a moderating variable. The data used in this study is secondary data taken from the annual financial statements of several property and real estate companies listed on the Indonesia Stock Exchange for 2020, 2021 and 2022. The sample in this study obtained 54 data from 18 selected companies using a purposive sampling technique. This study uses quantitative analysis methods, and the data analysis techniques used in this study are multiple regression equations and Moderated Regression Analysis (MRA). The results of this study indicate that Special Relationship Sales Transactions do not affect Tax Aggressiveness, while Special Relationship Lending Transactions have a positive effect on Tax Aggressiveness. Then Institutional Ownership cannot moderate the effect of special relationship sales transactions and special relationship lending transactions on tax aggressiveness.